A Critical Analysis of the Impacts of Financial Literacy and NPM on Village Funds Initiative in Indonesia. Issue 4 (12th March 2021) - Harun, Harun; Graham, Peter; Kamase, Haryono P.; Mir, Monir
ABSTRACT: Since 1999 the Indonesian government has adopted a more democratic and autonomous political system to prevent national disintegration and reduce the economic 'divide' that has appeared in society. To support the policy, the government introduced the Village Funds Initiative in 2014. This study examines how the initiative has been ineffective and riddled with problems due to structural challenges including low financial literacy, complicated budgetary and reporting systems and corruption. The study reminds policy-makers the dangers of NPM (New Public Management) ideology which derived from neoliberal philosophy, and subsequently used in decentralization programs without considering local issues within an individual country.